Koselleck, memory and history. Difficulties understanding the present - Gómez Ramos, Antonio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This article analyses Koselleck’s relation to the socio-political categories emerging with the new temporality in the last decades – particularly the notion of negative memory. Although Koselleck was recognized as a theorist of Modernity and is a reference thinker for many critics and interpreters of this new chronotope following the crisis of modernity, he does not fit into the new chronotope. After reviewing some interpretations of the present time, such as Hartog’s presentism, German compensation theory, Gumbrecht’s extended present and Assmann’s politics of memory, Koselleck’s late texts on negative memory are analysed. As he insisted on opposing memory to history, he had a critical stance to the present. Ironically, his courage in confronting recent German history brings him away from recent politics of memory. For this reason also, he was unable to interpret and understand the new chronotope.